مفهوم الذات متعدّد الأبعاد دراسة ميدانية على طلاب السنوات الأخيرة في كلية التربية بجامعة تشرين2011-2012 - أحمد نازك (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
سلط البحث الضَّوء على أهميّة دراسة وقياس مفهوم الذَّات بأبعاده المختلفة لأهمية المفهوم لضمان الصّحة النَّفسيّة لأفراد يشكِّلون القاعدة الأساسيّة لمجتمع سليم, ولدوره الأساسي في نمو الشَّخصيّة وتطورها مما ينعكس بشكل إيجابي على المجتمع, هادفاً إلى معرفة ما إذا كان مفهوم الذَّات يتأثَّر ويتغيّر من حيث الجنس ومكان الإقامة, وقد ورد في منحى البحث بعض النَّظريات والآراء التي تطرقت لدراسة وتعريف مفهوم الذات. والصّعوبات التي تكمن في قياس هذا المفهوم. وقد تمَّ استخدام مقياس مفهوم الذَّات متعدّد الأبعاد من خلال عملية مسح أنماط متعدّدة من السّلوك الّذي يدلُّ على كثير من جوانب مفهوم الذَّات وذلك بعد العودة للصَورة الأوليّة لهذا المقياس حيث كان عدد العبارات في الصورة الأولية (136)عبارة أمَّا في صورة المقياس المعدَّلة فقد أصبح عدد العبارات(88)عبارة. وتم استخدام قوانين من البرنامج الإحصائي (spss) منها قانون الترابط وقانون (ت ستودنت) لمعرفة الفروقات, وقد كانت النتائج في مجالي مفهوم الذات لحل المشكلات ومفهوم الذات للعلاقات مع الجنس الآخر لصالح الذكور, أما مفهوم الذات الجسدي فقد كانت الفروق لصالح الإناث, كذلك كانت النتائج لصالح ذكور المدينة في مجالات مفهوم الذات للعلاقات مع الجنس الآخر وفي مجال مفهوم الذات الأكاديمي وفي مجال مفهوم الذات ككل. وقد تم تقديم بعض المقترحات التي من الممكن أن تفيد في إضافة دراسات جديدة تعطي نتائج جديدة من الممكن مقارنتها مع غيرها من نتائج الدراسات. The research highlights the significance of studying and assessing the multidimensional concept of the self so as to guarantee the psychological health of the individuals who form the basis of a well-being society, and its essential role in personality development that positively reflects on society. It tends to make certain whether the concept of the self changes according to sex and residence. A few theories and approaches on the definition of the self have been mentioned, next to the potential difficulties while assessing such a concept. After getting back to its first image, a multidimensional scale of the self has been used through surveying multiple forms of behaviour that designated the various forms of the concept of self; where the number of the expressions in the first image was (136). In the modified image of scale, the number changes into (88) expressions. However, in order to determine the differences, a few principles of the statistics programme (spss) have been used such as the principle of correlation, and T-Student. Results in both concepts of the self for resolving problems and the self for establishing relations with the other sex, were in favour of the males. But the concept of the physical self reveals that differences were in favour of the females. So were the results in favour of the males in both concepts of the self for relationships with the other sex, and the academic self, and in the concept of the self as a whole. A few recommendations have been proposed that may support other latest researches which leads to some conclusions that make possible its comparison with other researches’ results.